2021
DOI: 10.22481/rsc.v16i3.4281
|View full text |Cite
|
Sign up to set email alerts
|

Estimulação Elétrica Neuromuscular Na Diástase, Flacidez E Trofismo Da Musculatura Abdominal: Uma Revisão Sistemática

Abstract: Objetivo: Realizar uma revisão sistemática da literatura, analisando os estudos que apontem os efeitos da eletroestimulação na diástase abdominal, flacidez e hipotrofismo da musculatura abdominal. Métodos: Para tanto, foi realizada a busca de artigos experimentais e ensaios clínicos com base nas publicações acessíveis nas bases de dados MEDLINE/PubMED, SciELO, PEDro e Google acadêmico, incluindo no estudo artigos relacionados ao tema proposto e que tinham como objetivo de estudo a influência da eletroterapia n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
1
2
0
3
Order By: Relevance
“…Among the included clinical trials, most obtained improvement in strength and increased cross-sectional area of the multifidus, transverse abdominis, and internal oblique muscles in patients with CLBP treated with NMES. Other articles that also made use of NMES applied on such muscles in sedentary individuals without diseases 25,26 corroborate the findings of improvement in the aspects of muscle function.…”
Section: Discussionsupporting
confidence: 54%
“…Among the included clinical trials, most obtained improvement in strength and increased cross-sectional area of the multifidus, transverse abdominis, and internal oblique muscles in patients with CLBP treated with NMES. Other articles that also made use of NMES applied on such muscles in sedentary individuals without diseases 25,26 corroborate the findings of improvement in the aspects of muscle function.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, studies show that there are different types of physiotherapy interventions for the treatment of abdominal diastasis, however, the subject is still scarce in the databases, making necessary practical studies on the subject, and reinforces even more the importance of physiotherapy, and this integrative literature review (CAMILO IR, et al ,2020).…”
Section: Randomized Studymentioning
confidence: 90%
“…According to the data collected, it was concluded that neuromuscular electrostimulation has a beneficial response, improving the strength and tone of the muscles that are requested. In addition, the technique excludes the need for women to perform high intensity exercises, especially in the puerperal period or for those who do not feel like performing intense exercises (CAMILO IR, et al, 2020).…”
Section: Randomized Studymentioning
confidence: 99%